2022
DOI: 10.1021/acs.langmuir.2c00949
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Liquid Film in Heterogeneous Condensation of Water Vapor: Effects of Solid–Fluid Interaction and Sulfuric Acid Component

Abstract: Understanding the phenomenon of filmwise condensation on solid surfaces is vital for industrial processes such as air pollutant control and desalination. In this work, we study the formation of condensed liquid films via molecular dynamics simulations, and the effects of solid−fluid interactions and the sulfuric acid component are given major attention. Water is chosen as the fluid, while the solid−fluid interaction is modified to characterize different solid surfaces. The results show that as the solid−fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Experimental studies have revealed that many forms of droplet manipulation can also be achieved using specially structured bionic surfaces . For phase-change properties, surface wettability is crucial for liquid condensation phenomena, , and carbon nanotubes have an important effect on the boiling of internal liquids. , In general, solid surface properties play an important role in the manipulation of nanodroplets.…”
mentioning
confidence: 99%
“…Experimental studies have revealed that many forms of droplet manipulation can also be achieved using specially structured bionic surfaces . For phase-change properties, surface wettability is crucial for liquid condensation phenomena, , and carbon nanotubes have an important effect on the boiling of internal liquids. , In general, solid surface properties play an important role in the manipulation of nanodroplets.…”
mentioning
confidence: 99%